1993
DOI: 10.1161/01.hyp.22.3.323
|View full text |Cite
|
Sign up to set email alerts
|

Renal sodium excretion in sons of hypertensive parents.

Abstract: The objective of this study was to evaluate whether renal excretion of sodium is impaired and whether tubular reabsorption of sodium is increased in normotensive white men with a familial predisposition to develop essential hypertension. We compared 11 normotensive sons of two hypertensive parents (SOHT) with 11 normotensive sons of two normotensive parents (SONT); renal sodium handling was assessed after 1 week of low-sodium diet ( A prevailing hypothesis to explain the familial predisposition to essential hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0
1

Year Published

1994
1994
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 18 publications
2
6
0
1
Order By: Relevance
“…9,10,17,18 Considering these data from backcrossed SHR, Y chromosome from a male rat with hypertension is responsible in part for elevation of BP probably through enhanced adrenergic nerve system or androgen receptor mediated events. 11,19 If hypertensive Y chromosome influences adrenergic nerve activity in human as well, [12][13][14][15] this theory is able to explain the linkage between the genetic loading from a hypertensive father and BMI observed in the present study. In this context, we demonstrated in the present study that heart rate is one of the predictors of SBP in the male students having a hypertensive father.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…9,10,17,18 Considering these data from backcrossed SHR, Y chromosome from a male rat with hypertension is responsible in part for elevation of BP probably through enhanced adrenergic nerve system or androgen receptor mediated events. 11,19 If hypertensive Y chromosome influences adrenergic nerve activity in human as well, [12][13][14][15] this theory is able to explain the linkage between the genetic loading from a hypertensive father and BMI observed in the present study. In this context, we demonstrated in the present study that heart rate is one of the predictors of SBP in the male students having a hypertensive father.…”
Section: Discussionsupporting
confidence: 55%
“…More interestingly, higher levels of BP in the offspring of hypertensive parents are often associated with an increase in plasma insulin concentrations or a decrease in insulin sensitivity and increased response of adrenergic nervous system to mental stress. [9][10][11]14,15 In fact, Scherrer et al 16 have demonstrated the relationship between BMI and the rate of sympathetic nerve discharge to skeletal muscle vasculature in normotensive subjects. In this context, we have demonstrated in our previous study that BP levels are well correlated to BMI in non-obese, normotensive freshman students having both hypertensive parents, and that such offspring have relatively higher plasma insulin concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Was die renale Natriumausscheidung anbetrifft, wurden in verschiedenen experimentellen Ansätzen keine relevanten Unterschiede zwischen gesunden Probanden mit und ohne hypertensiver Familienanamnese gefunden (9,51,27). Andererseits sind salzsensitive Nachkommen von Hypertonikern auch insulinresistent, was einen Zusammenhang von Natriumhaushalt und Insulinresistenz nahelegt (48).…”
Section: Kardiovaskuläre Dysregulation Bei Gesunden Nachkommenunclassified
“…Previous studies have speculated on sources of variability based on collection methods, but have failed to investigate specific physiological sources as potential contributors to this variability. The transport of Na + , K + , and Cl − into the intracellular space across the basolateral membrane of epithelial cells is influenced by blood ion levels 14. Altering the driving force for ion transport by changing the electrochemical gradient could thereby affect the airway surface liquid ion composition and the reflection of its composition in the EBC collections by influencing apical ion and water movement.…”
Section: Introductionmentioning
confidence: 99%